Peran Perempuan Dalam Dakwah Digital: Peluang Dan Tantangan - Nur Kholifah; Murodi; Muhamad Ardiansyah; Septiyadi; Salma Nur Zahro Maharani (STAI Bumi Silampari, 2025)
This study aims to explore the role of women in the context of digital da'wah, which has increasingly developed alongside advancements in information technology. The research focuses on three main aspects: (1) the concept of digital da'wah, (2) the role of women in digital da'wah, and (3) the opportunities and challenges faced by women in conducting da'wah through digital platforms. Using a qualitative approach and literature study, the research finds that digital da'wah is a form of religious communication that utilizes digital media—such as social media and other online platforms—to reach a broader and more diverse audience. In this context, women play a significant role, not only as content consumers (objects of da'wah) but also as producers and disseminators of religious messages (subjects of da'wah). They use digital platforms to convey religious messages, initiate discussions, and build communities centered around religious values. However, this role is not without challenges, including social stigma, limited access to technology, and pressure from cultural norms that continue to marginalize women. On the other hand, digital da'wah presents significant opportunities for women to actively participate in spreading religious values, building networks, and expanding their influence in the public sphere. This study concludes that digital da'wah opens new spaces for women to play a more active role in religious activities, although various challenges must still be addressed.